African Identity and Diasporic Consciousness in Teju Cole's Open City (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2026)
This study examines the construction and transformation of African identity in Teju Cole’s Open City through the theoretical lens of Afropolitanism. It examines how migration, cultural memory, pre-migration socialisation, and diasporic consciousness shape the identity of Julius, the novel's protagonist. Drawing on Afropolitan discourse, the study explores the tension between rooted African cultural values and the realities of global mobility for Africans abroad. It argues that African identity is neither fixed nor singular but remains dynamic and pluralistic within changing historical and social contexts. Through a close textual analysis of the novel, the study reveals that Julius's early exposure to Yoruba cultural traditions and communal values is undermined by traumatic personal experiences and emotional alienation, leading to an unstable sense of belonging before he migrated to the United States. His subsequent encounters with racial discrimination, cultural hybridity, and social isolation further complicate his identity, producing a fragmented Afropolitan consciousness that is neither wholly African nor fully Western. The study concludes that Open City challenges essentialist notions of identity by presenting the African identity as an evolving construct shaped by memory, history, migration, and individual experience
Keywords: African Identity, Afropolitanism, Diasporic Consciousness, Colonialism, Racial Discrimination